Functional analysis of PHYB polymorphisms in Arabidopsis thaliana collected in Patagonia - Ruiz-Diaz, María Jimena; Matsusaka, Daniel; Cascales, Jimena; Sánchez, Diego H.; Sánchez-Lamas, Maximiliano; Cerdán, Pablo D.; Botto, Javier F. (Frontiers in Plant Science, 2022)
Arabidopsis thaliana shows a wide range of natural genetic variation in light responses. Shade avoidance syndrome is a strategy of major adaptive significance that includes seed germination, elongation of vegetative structures, leaf hyponasty, and acceleration of flowering. Previously, we found that the southernmost Arabidopsis accession, collected in the south of Patagonia (Pat), is hyposensitive to light and displays a reduced response to shade light. This work aimed to explore the genetic basis of the shade avoidance response (SAR) for hypocotyl growth by QTL mapping in a recently developed 162 RIL population between Col-0 and Pat. We mapped four QTL for seedling hypocotyl growth: WL1 and WL2 QTL in white light, SHADE1 QTL in shade light, and SAR1 QTL for the SAR. PHYB is the strongest candidate gene for SAR1 QTL. Here we studied the function of two polymorphic indels in the promoter region, a GGGR deletion, and three non-synonymous polymorphisms on the PHYB coding region compared with the Col-0 reference genome. To decipher the contribution and relevance of each PHYB-Pat polymorphism, we constructed transgenic lines with single or double polymorphisms by using Col-0 as a reference genome. We found that single polymorphisms in the coding region of PHYB have discrete functions in seed germination, seedling development, and shade avoidance response. These results suggest distinct functions for each PHYB polymorphism to the adjustment of plant development to variable light conditions.